Conceptualizing theworkcation perceived attributes, concepts and impacts among local employees / Mohamad Zaidi Abdul Hamid and Hassnah Wee - Abdul Hamid, Mohamad Zaidi; Wee, Hassnah (Universiti Teknologi MARA, Sabah, 2023)
The study aims to discover the perceived attributes, concepts, and impacts of workcation among local employees. A total of 242 study participants were chosen using purposive convenience sampling techniques. An online Google form was used to collect 150 usable responses. The data for this study were analysed using descriptive statistics. Results found travelling for official company affairs was the key attribute of workcation. Employee retention, productivity and creativity were the three most apparent perceived impacts of workcation. The workcation concept is viable for implementation by employers due to its flexibility and enhances employees' creativity elements. The findings of this study assist local employees in understanding the attributes, concepts, and potential impact of implementing the workcation, which will be more beneficial if implemented as part of the company's work culture. Future studies can extend this research and validate the workcation concept in a different setting.